Novel core–shell CHX/ACP nanoparticles effectively improve the mechanical, antibacterial and remineralized properties of the dental resin composite. Issue 4 (April 2021) - Yang, Yanwei; Xu, Zexian; Guo, Yuqing; Zhang, Hongchen; Qiu, Yinong; Li, Jianxue; Ma, Dongyang; Li, Zhiqiang; Zhen, Ping; Liu, Bin; Fan, Zengjie
Abstract: Objective: The core–shell chlorhexidine/amorphous calcium phosphate (CHX/ACP) nanoparticles were synthesized and used to modify the dental resin composite, aiming to improve its remineralized and antibacterial properties. Methods: The core–shell CHX/ACP nanoparticles were synthesized by vesicle-templating technology and characterized, and their sustained release and antibacterial properties were also evaluated. Subsequently, the synthesized nanoparticles were incorporated into the dental resin composite at 1 wt.%, 5 wt.% or 10 wt.% to obtain different experimental groups. The physical properties, including curing depth, double bond conversion rate, water absorption and solubility, the sustained-release effects, and mechanical properties of the modified resin composite were evaluated. The remineralization ability was also measured by SEM. The antibacterial experiment of the modified resin composite with fresh preparation or aging in water for 28 days was carried out by a plate count method. Results: The physical and chemical characterizations showed that the synthesized nanoparticles presented a core–shell structure, and their diameter was about 98.5 nm. The shell was composed of ACP with the core full of CHX. These nanoparticles had a release effect on calcium, phosphate ions, and CHX. The nanoparticles could effectively inhibit the growth of S. mutan at a lower concentration (≥50 μg/mL). The curing depth, the double bond conversion, the water absorption, the solubility, the flexural strength, the flexural modulus, and the compressive strength of the modified resin composite were 3.86–4.88 mm, 62.32–73.61%, 1.47–2.84%, 0.21−0.48%, 45.83–109.46 MPa, 2.57–4.91 GPa, and 66.43–160.38 MPa, respectively. The modified resin composite containing 5 wt.% and above CHX/ACP nanoparticles could effectively inhibit the growth of S. mutans regardless of aging in water, with immediate and aging antibacterial rate of more than 92%. In addition, the modified resin composite had a certain remineralization property in the SBF solution verified by SEM. Significance: The core–shell CHX/ACP nanoparticles were successfully prepared and used to modify the resin composite. The modified dental resin composite with 5 wt.% CHX/ACP nanoparticles had excellent mechanical, antibacterial, and remineralization properties. It is expected to be an ideal restorative filling material for clinical application.